2010
DOI: 10.1186/1750-1326-5-47
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson-related parkin reduces α-Synuclein phosphorylation in a gene transfer model

Abstract: Backgroundα-Synuclein aggregates in Lewy bodies and plays a central role in the pathogenesis of a group of neurodegenerative disorders, known as "Synucleinopathies", including Parkinson's disease. Parkin mutations result in loss of parkin E3-ubiquitin ligase activity and cause autosomal recessive early onset parkinsonism.ResultsWe tested how these two genes interact by examining the effects of parkin on post-translational modification of α-Synuclein in gene transfer animal models, using a lentiviral gene deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 50 publications
7
77
0
Order By: Relevance
“…Another protective role of Parkin against α-synuclein toxicity in PD would be the reduction in the Parkin-induced phosphorylation state of α-synuclein, which would reduce α-synuclein aggregation (Khandelwal et al, 2010). Mutations in LRRK2…”
Section: Linking Oxidative Stress and Mitochondrial Dynamics In Pd Amentioning
confidence: 99%
“…Another protective role of Parkin against α-synuclein toxicity in PD would be the reduction in the Parkin-induced phosphorylation state of α-synuclein, which would reduce α-synuclein aggregation (Khandelwal et al, 2010). Mutations in LRRK2…”
Section: Linking Oxidative Stress and Mitochondrial Dynamics In Pd Amentioning
confidence: 99%
“…Although the effect of phosphorylation at S129 has been investigated in rat (Gorbatyuk et al, 2008;Azeredo da Silveira et al, 2009;McFarland et al, 2009) and fly models of PD (Chen and Feany, 2005), the role of S87 phosphorylation in ␣-syn fibrillogenesis, LB formation and neurotoxicity in vivo remains unexplored. A recent study by Khandelwal et al (2010) demonstrated that overexpression of parkin protects against ␣-syn-induced toxicity by reducing the levels of both pS87 and pS129 in vivo, suggesting that phosphorylation at these residues is a pathological event.…”
Section: Introductionmentioning
confidence: 99%
“…And in the rat striatum, α ‐synuclein overexpression using viral vector‐mediated gene transfer results in decreased expression of PP2A B and C subunits as well as decreased PP2A activity. This effect is associated with increased α ‐synuclein phosphorylation and aggregation as well as neuronal cell death and inflammation 48. Interestingly, parkin, which is linked to recessively inherited PD due to loss of function mutations, reportedly prevents α ‐synuclein‐mediated reduction in PP2A expression and activity and mitigates the pathology induced by α ‐synculein 48.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is associated with increased α ‐synuclein phosphorylation and aggregation as well as neuronal cell death and inflammation 48. Interestingly, parkin, which is linked to recessively inherited PD due to loss of function mutations, reportedly prevents α ‐synuclein‐mediated reduction in PP2A expression and activity and mitigates the pathology induced by α ‐synculein 48. The negative impact of impaired PP2A activity is also exerted on parkin functioning as well contributing to neuronal dyshomeostasis.…”
Section: Discussionmentioning
confidence: 99%